Edelman's health promotion throughout the life span - Kudzma, Elizabeth Conelly; LaRocco, Susan A.; Natale, Susan (St. Louis, Missouri Elsevier, 2026)
Edelman’s Health Promotion Throughout the Life Span, 11th Edition, provides comprehensive coverage of leading health promotion concepts, from assessment to interventions to application. Its lifespan approach addresses patients’ unique needs with case studies and care plans presented within an assessment framework based on Gordon’s Functional Health Patterns. Addressing each age and stage of development, this market-leading text covers the latest research and trends in health promotion and disease prevention for diverse population groups.
Includes bibliographical references and index.
Keywords: Health promotion .; Health education